Analisis Literasi Kemaritiman Buku Ajar PAI di SDN Tanjung Mas Semarang - Ahmad Umam Aufi (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2024)
Textbooks as an important component of learning are often overlooked in the process of adapting to changes in the Merdeka curriculum, especially those related to contextual principles. This study analyzes maritime literacy in the Merdeka curriculum textbooks in Islamic religious education subjects at SD N Tanjung Mas Semarang as an embodiment of contextual principles. This study uses library research methods by collecting data through interview and documentation techniques. In analyzing the data, researchers used content analysis to explore contextual principles in the form of maritime literacy in the textbook. The results of this research indicate that maritime literacy has not been found in the independent curriculum textbooks used in Islamic religious education subjects at SDN Tanjung Mas Semarang. Maritime literacy is presented by educators by inserting material about the culture of coastal Muslim communities, Muslim attitudes towards the sea and the urgency of protecting the sea. This research recommends that academics and teachers develop a maritime-oriented textbook for students in coastal areas.